Robert Frost and New England : the poet as regionalist - Kemp, John C. (Princeton legacy library., 1979)
Though critics traditionally have paid homage to Robert Frost's New England identity by labeling him a regionalist, John Kemp is the first to investigate what was in fact a highly complex relationship between poet and region. Through a frankly revisionist interpretation, he not only demonstrates how Frost's relationship to New England and his attempt to portray himself as the ""Yankee farmer poet"" affected his poetry; he also shows that the regional identity became a problem both for Frost and for his readers. Originally published in 1979. The Princeton Legacy Library uses the latest print.